UDS in CAN flash programming. Issue 6 (April 2019) - Du, Li; Xie, Peng; Zhou, Bing; Yu, Yongyan; Wan, Juan; Hu, Haixia; Cui, Lianghao
Abstract: Flash bootloader is the most important part in the ECU platform software. It is the base function of the product in developing and after-sale, supporting self-flash. CAN bus is the main network in vehicle, which connect the whole network together. Thus, flash programming through CAN bus, bring us convenient in whole vehicle flashing.